Pattern of Periodontitis among Adult Patients Attending at Medical University of Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Periodontitis is one of the most common oral diseases and is one of the widest spread chronic diseases all over the world. If a person maintains a good oral hygiene, he/she can control periodontitis easily. Periodontitis is a preventable disease.Objectives: This study was aimed to know the current pattern, the possible causes and the attitude towards periodontitis among adult patients attending at outdoor of dental faculty of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh.Methodology: This cross-sectional study was carried out in the OPD of Dental faculty of BSMMU, Dhaka fromJanuary 2013 to December 2013 over a period of one year. One hundred twenty patients with any sort of dental problem were enrolled in this study.Results: The current study depicted that 68.3% of the patients were from age group of 18 to 40 years and 59.2% were male while 40.8% were female. Most of the respondents (65.8%) lived in urban area. This study showed that 80.8% experienced bleeding from gums and 59.2% had knowledge about cleaning teeth before going to bed and after breakfast. It was found that 77.5%of the respondents used tooth brush and tooth paste for cleaning their teeth. Only 15.8% of the respondents visited dentist for oral and dental check-up regularly. According to life style related habit, 53(44.2%) respondents were smoker, 55 (45.8%) respondents chewed betel leaf and 30 (25%) of the respondents hewed betel leaf with Jarda or SadaPata. Majority 104 (86.7) had calculus, defective margins and restorations. Most of the respondents (95.0%) had bleeding on probing.Conclusion: In this study a significant number of respondents have periodontitis who have attended outdoor of dental faculty. Older age, smoking, betel, jarda/sadapata, diabetes mellitus and presence of calculus and restorations are the risk factors for developing periodontitis.Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 76-80